Willingness to Pay and Consumer Acceptance Assessment for Clean Cooking in Uganda - Lascurain, Javier; Jagoe, Kirstie Anne; van Tilborg, Caroline (World Bank, Washington, DC, 2015)
This report addresses the need to increase market penetration of clean stoves with the end goal of reducing household air pollution and the associated disease burden as well as to reduce nonrenewable biomass fuel consumption. The first step in this goal is identifying suitable cleaner cooking technologies for the Ugandan market. A second step is ensuring that the cleaner cooking technologies are adopted to materialize reductions in indoor air pollution and biomass fuel consumption. A third step is to find suitable models and marketing strategies to introduce these technologies into households. A final step is ensuring that these technologies are adopted in the long term or are replaced by cleaner technologies. The different intervention stove models presented important differences in fuel savings and willingness to pay (WTP). The WTP estimates are based on actual demand for stoves under the experiment conditions. The Becker-deGroot-Marschak method failed to capture accurate demand estimates and WTA estimates do not reflect the population’s purchase capacity. Hence, the actual purchase stoves’ using randomized prices was used to more accurately measure demand.